Urinary Urea Excretion and Long-term Outcome After Renal Transplantation. Issue 5 (May 2015) - Deetman, Petronella E.; Said, M. Yusof; Kromhout, Daan; Dullaart, Robin P.F.; Kootstra-Ros, Jenny E.; Sanders, Jan-Stephan F.; Seelen, Marc A.J.; Gans, Rijk O.B.; Navis, Gerjan; Joosten, Michel M.; Bakker, Stephan J.L.
Abstract : Background: Little is known about optimal protein intake after transplantation. The aim of this study was to prospectively investigate associations of urinary urea excretion, a marker for protein intake, with graft failure and mortality in renal transplant recipients (RTR) and potential effect modification by body mass index (BMI) and estimated glomerular filtration rate (eGFR). Methods: Urinary urea excretion was measured in repeated 24-hr urine collections between 6 and 18 months after transplantation. Results: In total, 940 RTR were included. During 4.4 (2.3–7.8) years of follow-up for graft failure and 4.8 (2.5–8.3) years for all-cause mortality, 78 RTR developed graft failure and 158 RTR died. Urinary urea excretion was not associated with graft failure in the overall population, but was inversely associated with graft failure in RTR with BMI less than 25 kg/m 2 (hazard ratio [HR], 0.64 [0.28–1.50] and 0.27 [0.09–0.83] for the second and third tertiles, respectively, P < 0.001), and in RTR with eGFR of 45 mL per min per 1.73 m 2 or higher (HR, 0.34 [0.15–0.79], P = 0.015 and HR, 0.31 [0.11–0.86], P = 0.025 for the second and third tertiles, respectively), both independent of potential confounders. Compared to the first tertile, RTR in the second and third tertiles of urinary urea excretion were at a lower risk of all-cause mortality (HR, 0.47 [0.32–0.69]; P < 0.001 and HR, 0.42 [0.26–0.68]; P < 0.001, respectively), independent of potential confounders. Body mass index and eGFR did not influence this association. Conclusion: Urinary urea excretion, a marker for protein intake, was inversely related to graft failure in RTR with BMI less than 25 kg/m 2 and in RTR with an eGFR of 45 mL per min per 1.73 m 2 or higher. In addition, urinary urea excretion was inversely related to mortality. Abstract : Urinary urea is a marker for protein intake. In this long-term study, urinary urea excretion was inversely proportional to patient and graft survival, yet independent of eGFR and BMI. Thus normal protein intake may be beneficial for outcomes. Supplemental digital content is available in the text.